Hardware and software : verification and testing : 12th International Haifa Verification Conference, HVC 2016, Haifa, Israel, November 14-17, 2016, Proceedings /: verification and testing : 12th International Haifa Verification Conference, HVC 2016, Haifa, Israel, November 14-17, 2016, Proceedings. ([2016]) - Unknown
No abstract available